High-Level Aminoglycoside Resistance and Distribution of Aminoglycoside Resistant Genes among Clinical Isolates of Enterococcusin a Tertiary Care Hospital - Priyanka Paul Biswas; Anamika Singh; Sangeeta Dey; Farhaan Fidai; Mohammad Hassan Bin Ozair; Aninda Sen (International Journal of Health and Clinical Research, 2022)
Objectives: The aim of study was to determine the susceptibility of clinical isolates of Enterococcus species to high level aminoglycoside by MIC test and the presence of five different aminoglycoside modifying genes [AMEs]. Methods: Enterococci were isolated from various clinical samples. High level resistance to gentamicin and streptomycin was done by high potency disc diffusion method [HPDDM]. Screenings to both the antibiotics were done by agar screen method [ASM]. Minimum Inhibitory Concentration [MIC] was determined by Agar Dilution Method [ADM]. Multiplex PCR was used to detect the presence of AME genes. Results: 21.4% [24/112] and 25.8% [29/112] strains were resistant to gentamicin and streptomycin by ASM. A total of 32.2% [36/112] were found to be HLGR with MIC > 512μg/ml. 29 strains were found to show resistance to streptomycin with MIC i.e. ≥ 2048 μg/ml.aac(6′)-Ie-aph(2′′)-Ia gene was found in 16.9% [19/112] of enterococcal isolates. Moreover, 4.5% (5/112) of the Non-HLAR strains with MIC [256 μg/ml] expressed aac(6′)-Ie-aph(2′′)-Ia gene. Newer AME genes like aph(2′′)-Ic&aph(2′′)-Id were detected in 4.5% [5/112] and 5.4% [6/112] strains. The predominant virulence gene in HLAR was hyl gene [44.1%; 30/68]. Conclusions: The study concluded that the AMEs have disseminated amongst the non-faecalis non-faecium strains in this region. The number of aac(6”)-Ie-aph(2”)-Ia genes detected by PCR was less as compared to those detected by MIC test, it should be taken into consideration that due to the intrinsic limitations of any PCR assay, a negative result may not always signify the absence of a gene altogether in enterococcus.